A DNA-fuelled molecular machine made of DNA. - Yurke, B; Turberfield, A; Mills, A; Simmel, F; Neumann, J (2000)
Molecular recognition between complementary strands of DNA allows construction on a nanometre length scale. For example, DNA tags may be used to organize the assembly of colloidal particles, and DNA templates can direct the growth of semiconductor nanocrystals and metal wires. As a structural material in its own right, DNA can be used to make ordered static arrays of tiles, linked rings and polyhedra. The construction of active devices is also possible--for example, a nanomechanical switch, whose conformation is changed by inducing a transition in the chirality of the DNA double helix. Melting of chemically modified DNA has been induced by optical absorption, and conformational changes caused by the binding of oligonucleotides or other small groups have been shown to change the enzymatic activity of ribozymes. Here we report the construction of a DNA machine in which the DNA is used not only as a structural material, but also as 'fuel'. The machine, made from three strands of DNA, has the form of a pair of tweezers. It may be closed and opened by addition of auxiliary strands of 'fuel' DNA; each cycle produces a duplex DNA waste product.